THE CORRELATION BETWEEN THE SELF-DIRECTED LEARNING AND READING COMPREHENSION AT UNIVERSITAS RIAU - Geblyna Putri; Mahdum Mahdum; Dahnilsyah Dahnilsyah (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2023)
This research aimed to find out the correlation between self- directed learning and reading comprehension of the fifth- semester students of the English department of FKIP Universitas Riau. The researchers used a descriptive quantitative method as the data approach. The samples of this research were 74 students from the fifth-semester students of the English department of FKIP Universitas Riau. The research instruments are a questionnaire and a test. The questionnaire is for the data on self-directed learning while the test is for the data on reading comprehension. To analyze the data, the researchers employed SPSS Statistics 25. The data analysis showed that the mean score of the student's self-directed learning is 215.18, classified as moderate level, while the mean score of the student's reading comprehension is 56.35, categorized as moderate level. Moreover, the research finding showed the correlation coefficient of the two variables is 0.694, indicating a positive and moderate correlation. Also, the determinant coefficient is 0.48 which implies self-directedlearning has a 48% influence on the students’ reading comprehension, leaving the other 52% to other factors. After finding that there is a moderate relationship between self- directed learning and reading comprehension, it is suggested that students should apply self-directed learning activities well, for it can result in better reading comprehension. This is mainly because self-directed learning gives them the freedom to choose their own reading materials and learning objectives.